An overview of the factors affecting fiber-optic communication lines during lightning discharges and modeling of laboratory installations designed to study the effect of a magnetic field on fiber parameters - V. E. Mitrokhin; V. E. Osipov (Омский научный вестник)
The article provides an overview of the known effects that influence the transmission of information over optical fiber and that arise as a result of lightning discharges: the electro-optical Kerr effect, the Faraday effect, the influence of ionizing radiation. It is indicated that there is preliminary empirical data according to which the magnetic field changes such an optical fiber parameter as attenuation. In order to verify these preliminary empirical data, further experimental studies of the supposed influence of the magnetic field on attenuation are proposed, for which it is necessary to build a laboratory installation. This article is also devoted to a comparison of various options for laboratory installations and the preliminary selection of a parameter for comparison. As a result of modeling two options for a laboratory installation and comparing them according to the accepted parameter, one of two installation options is selected.